Assignment 19

#$&*

course Mth 158

4/2 11 pm

019. `* 19

*********************************************

Question: * 2.4.10 (was 2.4.30). (0,1) and (2,3) on diameter **** What are the center, radius and equation of the indicated circle?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: the center/midpoint is between the two endpoints

To find the midpoint, add x^1 and x^2 then divide by 2, then do likewise w/ y^1 and y^2

We get the midpoint of (1, 2)

Since we have the midpoint we can now get the equation

We use the general equation of a circle to also get the radius

(x - h)^2 + (y - k)^2 = r^2

Now apply the midpoint (1, 2) otherwise (h, k) to the equation

(x - 1)^2 + (y - 2)^2 = r^2

Now apply an endpoint to the equation- (0, 1)

(0 -1)^2 + (1 - 2)^2 = r^2 or

2 = r^2

So the radius of the circle is sqrt(2)

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: * *

The center of the circle is at the midpoint between the endpoints of the diameter, at x coordinate (0 + 2) / 2 = 1 and y coordinate (1 + 3) / 2 = 2. i.e., the center is at (1, 2).

Using these coordinates, the general equation (x-h)^2 + (y-k)^2 = r^2 of a circle becomes

• (x-1)^2 + (y-2)^2 = r^2.

Substituting the coordinates of the point (0, 1) we get

(0-1)^2 + (1-2)^2 = r^2 so that

r^2 = 2.

Our equation is therefore

• (x-1)^2 + (y - 2)^2 = 2.

You should double-check this solution by substituting the coordinates of the point (2, 3).

Another way to find the equation is to simply find the radius from the given points:

The distance from (0,1) to (2,3) is sqrt( (2-0)^2 + (3-1)^2 ) = sqrt(4 + 4) = sqrt(8) = 2 * sqrt(2).

This distance is a diameter so that the radius is 1/2 (2 sqrt(2)) = sqrt(2). *

The equation of a circle centered at (1, 2) and having radius sqrt(2) is

• (x-1)^2 + (y - 2)^2 = (sqrt(2)) ^ 2 or

• (x-1)^2 + (y - 2)^2 = 2

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating:

*********************************************

Question: * 2.4.14 / 16 (was 2.4.36). What is the standard form of a circle with (h, k) = (1, 0) with radius 3?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * The standard form of a circle is (x - h)^2 + (y - k)^2 = r^2, where the center is at (h, k) and the radius is r.

In this example we have (h, k) = (1, 0). We therefore have

(x-1)^2 +(y - 0)^2 = 3^2.

This is the requested standard form.

This form can be expanded and simplified to a general quadratic form. Expanding (x-1)^2 and squaring the 3 we get

x^2 - 2x +1+y^2 = 9

x^2 - 2x + y^2 = 8.

However this is not the standard form.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question: * 2.4.22 / 24 (was 2.4.40). x^2 + (y-1)^2 = 1 **** Give the center and radius of the circle and explain how they were obtained. In which quadrant(s) was your graph and where did it intercept x and/or y axes?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

From the equation we know that the center of the circle is at the point (0, -1)

We can also learn from the equation that the radius is 1

We can find the x intercept by setting y to 0 and solving for x

x^2 + (0 - 1)^2 = 1

x^2 + (-1)^2 = 1

x^2 +1 = 1

x^2 + 0

so the x intercept is (0, 0)

we can find the y intercept by setting the x value to 0

(y - 1)^2 = 1

Y - 1= +-1

If y -1 = -1 then

Y = 0

If y-1=1 then

Y = 2

So the y intercepts are (0, 0) and (0, -2)

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * The standard form of a circle is (x - h)^2 + (y - k)^2 = r^2, where the center is at (h, k) and the radius is r.

In this example the equation can be written as

(x - 0)^2 + (y-1)^2 = 1

So h = 0 and k = 1, and r^2 = 1. The center of the is therefore (0, -1) and r = sqrt(r^2) = sqrt(1) = 1.

The x intercept occurs when y = 0:

x^2 + (y-1)^2 = 1. I fy = 0 we get

x^2 + (0-1)^2 = 1, which simplifies to

x^2 +1=1, or

x^2=0 so that x = 0. The x intercept is therefore (0, 0).

The y intercept occurs when x = 0 so we obtain

0 + (y-1)^2 = 1, which is just (y - 1)^2 = 1. It follow that

(y-1) = +-1.

If y - 1 = 1 we get y = 2; if y - 1 = -1 we get y -2. So the y-intercepts are

(0,0) and (0,-2)

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

I’m confused about how y - 1 = -1 turns out to be y = -2… I thought you would add 1 to each side, which would give you 0. Of course, drawing the circle on the graph makes it obvious that the y-intercept is (0, -2), but I can’t figure out how to get that solution from the equation.

------------------------------------------------

Self-critique Rating:2

@&

You are correct.

The last two lines of the given solution should read as follows:

If y - 1 = 1 we get y = 2; if y - 1 = -1 we get y = 0. So the y-intercepts are

(0,0) and (0,-2)

*@

*********************************************

Question: * 2.4.32 / 34 (was 2.4.48). 2 x^2 + 2 y^2 + 8 x + 7 = 0 **** Give the center and radius of the circle and explain how they were obtained. In which quadrant(s) was your graph and where did it intercept x and/or y axes?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Relist the terms, grouping x and y terms together

2x^2 + 8x + 2y^2 = -7

Divide by the common factor 2

x^2 + 4x + y^2 = -7/2

complete the square of x^2 + 4x by adding 4 to each side

x^2 + 4x + 4 + y^2 = -7/2 + 4

now factor (x^2 + 4x + 4)

(x + 2)^2 + y^2 = ½

This equation give us a center point of (-2, 0)

The radius is sqrt(1/2)

To find the x-intercept y must equal 0

(x + 2)^2 + 0 = ½

(x + 2) = ± sqrt(1/2)

X = -2 ± sqrt(½)

If x= -2 + sqrt(½)

Then x = -1.3

If x= -2 - sqrt(½)

Then x = -2.7

So the x-intercepts are (-1.3, 0) and (-2.7, 0)

To find the y-intercepts x must equal 0

(0+2)^2 + y^2 = ½

4 + y^2 = ½

Y^2 = -3.5

Y^2 cannot be negative so there is no y-intercept

The graph is on the left side of the graph, half in the 1st quadrant and half in the 4th

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * We first want to complete the squares on the x and y terms:

Starting with

2x^2+ 2y^2 +8x+7=0 we group x and y terms to get

2x^2 +8x +2y^2 =-7. We then divide by the common factor 2 to get

x^2 +4x + y^2 = -7/2. We complete the square on x^2 + 4x, adding to both sides (4/2)^2 = 4, to get

x^2 + 4x + 4 + y^2 = -7/2 + 4. We factor the expression x^2 + 4x + 4 to obtain

(x+2)^2 + y^2 = 1/2.

We interpret our result:

The standard form of the equation of a circle is

• (x - h)^2 + (y - k)^2 = r^2,

where the center is the point (h, k) and the radius is r.

Matching this with our equation

• (x+2)^2 + y^2 = 1/2

we find that h = -2, k = 0 and r^2 = 1/2. We conclude that

• the center is (-2,0)

• the radius is sqrt (1/2).

To get the intercepts:

We use (x+2)^2 + y^2 = 1/2

If y = 0 then we have

(x+2)^2 + 0^2 = 1/2

(x+2)^2 = 1/2

(x+2) = +- sqrt(1/2)

• x + 2 = sqrt(1/2) yields x = sqrt(1/2) - 2 = -1.3 approx.

• x + 2 = -sqrt(1/2) yields x = -sqrt(1/2) - 2 = -2.7 approx

• (note: The above solutions are approximate. The exact solutions can be expressed according to the following:

• sqrt(1/2) = 1 / sqrt(2) = sqrt(2) / 2, found by rationalizing the denominator; so sqrt(1/2) - 2 = sqrt(2)/2 - 2 = (sqrt(2) - 4) / 2. This is an exact solution for one x intercept. The other is (-sqrt(2) - 4) / 2.

If x = 0 we have

(0+2)^2 + y^2 = 1/2

4 + y^2 = 1/2

y^2 = 1/2 - 4 = -7/2.

y^2 cannot be negative so there is no y intercept. This is consistent with the fact that a circle centered at (2, 0) with radius sqrt(1/2) lies entirely to the right of the y axis. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): I thought I did very well with this particular problem, but reading the solution, I find conflicting answers. At the beginning of the given solution, the center is listed as being (-2, 0), then, at the end it’s listed as (2, 0) and on the right side of the y-axis…both the x-intercepts are negative, and since the radius is sqrt(1/2) shouldn’t the center be (-2, 0)?

------------------------------------------------

Self-critique Rating:3

@&

Another typo.

The last two lines should read

y^2 cannot be negative so there is no y intercept. This is consistent with the fact that a circle centered at (-2, 0) with radius sqrt(1/2) lies entirely to the right of the y axis. **

*@

*********************************************

Question: * 2.4.40 / 30 (was 2.4.54). General equation if diameter contains (4, 3) and (0, 1). **** Give the general equation for your circle and explain how it was obtained.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

We need to find the midpoint between the two given points

The equation to find the midpoint:

((x1 + x2)/2, (y1 + y2)/2)

((4 + 0)/2, (3 + 1)/2)

(2, 2)

We can use the distance from the center to either of the given points to find the radius

(2 - 0)^2 + (2-1)^2 =r^2

So with this equation we have a radius of sqrt(5)

So our equation for the circle is

(x - 2)^2 + (y - 2)^2 = 5

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * The center of the circle is the midpoint between the two points, which is ((4+0)/2, (3+1)/2) = (2, 2).

The radius of the circle is the distance from the center to either of the given points. The distance from (2, 2) to (0, 1) is sqrt( (2-0)^2 + (2-1)^2 ) = sqrt(5).

The equation of the circle is therefore found from the standard equation, which is

• (x - h)^2 + (y - k)^2 = r^2,

where the center is the point (h, k) and the radius is r.

Since the center is at (2, 2) and the radius is sqrt(5), our equation is

(x-2)^2 + (y-2)^2 = (sqrt(5))^2 or

(x-2)^2 + (y-2)^2 = 5. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

@&

Very good.

You were correct with both of your notes. Check my inserted notes.

*@